PERBANDINGAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL 70% DAUN PEPAYA MUDA DAN TUA (CARICA PAPAYA L.) MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Mahesa Yudhantara, Sandi; Christina , Odilea Dea; Hastuti, Fitri (Universitas Duta Bangsa Surakarta, 2024)
The content of secondary metabolite compounds flavonoid that contained in papaya leaves (Carica papaya Leaf) has various benefits for treatment, but the utilization of flavonoid compounds contained in papaya leaves wasn't optimal due to the selection of sources that hasn't been optimal. One consideration that can be used as a benchmark for obtaining maximum benefits from papaya leaves is the age of the leaves. The aim of this study is to determine the effect of papaya leaf age on flavonoid content. The samples used in this research were young and old papaya leaves, where the extraction process used the maceration method using ethanol 70% as a solvent. Flavonoid content analysis was carried out qualitatively using thin layer chromatography and quantitatively using UV-Vis spectrophotometry. The results of determining total flavonoid between young and old papaya leaves resulted in lower levels in young leaves, where young leaves had a content of 8.15% w/w QE, while old leaves had a content of 17.41% w/w QE.